Acute Mesentero-Axial Gastric Volvulus in the Setting of a Paraesophageal Hernia: A Rare Case Report - Lefika Bathobakae MD, MPH; Mohita Jariwala BA; Ela Hajdarmataj MD; Ruhin Yuridullah MD; Gabriel Melki MD; Yana Cavanagh MD; Walid Baddoura MD (SAGE Publishing, 2023)
Acute gastric volvulus is a surgical emergency that requires urgent intervention to prevent gastric ischemia and necrosis. Gastric volvulus manifests as an abnormal rotation or torsion of the stomach and may be associated with gastric outlet obstruction. This pathology can be classified as either mesentero-axial or organo-axial volvulus, depending on the axis of rotation. Similarly, it can be categorized as primary or secondary, depending on the etiology. We describe a case of a 63-year-old female with a history of peptic ulcer disease who presented with severe epigastric pain and vomiting of one-day duration. She was diagnosed with an acute mesentero-axial gastric volvulus, which was successfully reduced using a nasogastric tube.